Calprotectin is a stronger predictive marker of relapse in ulcerative colitis than in Crohn's disease. (11th February 2005) - Costa, F; Mumolo, M G; Ceccarelli, L; Bellini, M; Romano, M R; Sterpi, C; Ricchiuti, A; Marchi, S; Bottai, M
Abstract : Background and aims: The clinical course of inflammatory bowel disease is characterised by a succession of relapses and remissions. The aim of our study was to assess whether the predictive value of faecal calprotectin—a non-invasive marker of intestinal inflammation—for clinical relapse is different in ulcerative colitis (UC) and Crohn's disease (CD). Methods: Seventy nine consecutive patients with a diagnosis of clinically quiescent inflammatory bowel disease (38 CD and 41 UC) were followed for 12 months, undergoing regular clinical evaluations and blood tests. A single stool sample was collected at the beginning of the study from each patient and the calprotectin concentration was assessed by a commercially available enzyme linked immunoassay. Results: In CD, median calprotectin values were 220.1 μg/g (95% confidence interval (CI) 21.7–418.5) in those patients who relapsed during follow up, and 220.5 μg/g (95% CI 53–388) in non-relapsing patients (p = 0.395). In UC, median calprotectin values were 220.6 μg/g (95% CI 86–355.2) and 67 μg/g (95% CI 15–119) in relapsing and non-relapsing patients, respectively (p<0.0001). The multivariate Cox (proportional hazard) regression model, after adjustment for possible confounding variables, showed a twofold and 14-fold increase in the relapse risk, respectively, in those patients with CD and UC in clinical remission who had a faecal calprotectin concentration higher than 150 μg/g. Conclusions: Faecal calprotectin proved to be an even stronger predictor of clinical relapse in UC than in CD, which makes the test a promising non-invasive tool for monitoring and optimising therapy.